Pemanfaatan Patogen Serangga (Beauveria bassiana Bals.) untuk Mengendalikan Hama Penghisap Buah Kakao (Helopeltis spp.) di Desa Gadungan, Kecamatan Selemadeg Timur, Kabupaten Tabanan - I WAYAN DIKSA GARGITA; I PUTU SUDIARTA; GUSTI NGURAH ALIT SUSANTA WIRYA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2017)
Utilization of Insect Pathogen (Beauveria bassiana Bals.) to Control the Suction Pest of Cocoa (Helopeltis spp.) in Gadungan Village,The District of East Selemadeg, Tabanan RegencyCultivation of cocoa has the potential to improve the economy of farmers. However, cocoa production has decreased due to Helopeltis spp. The control of Helopeltis spp. still use synthetic chemical pesticides that are harmful to the health of farmers, consumers and environmental pollution. Therefore, it needs to be done by eco-friendly control using Beauveria bassiana which is reported to be able to control some insect pests such as Helopeltis spp. Utilization of B. bassiana is usually in the form of formulations. The research was conducted to determine the quality formulations and efficacy of B. bassiana against Helopeltis spp. obtained from Dinas Perkebunan Provinsi Bali. The research method using randomized block design with 5 treatments, 5 replications and the treatment using concentration formulation 20 grams, 15 grams, 10 grams, 5 grams to dissolve in one liter of water and the control just using water. The observed variable is the number of former suction on fruit. The identification results showed the tested formulations made from active B. bassiana which is characterized by colonies are white, round-shape and the spore structure is like grapes with a good quality because it has spore density 1,06x107 spore/ ml. B. bassiana is quite effective to infect Helopeltis spp. because it just need 4 days to kill Helopeltis spp. The test results showed the concentration of 20 grams formulation is the best concentration with the fewest number of former suction on fruit.